Optimal management strategies of renewable energy systems with hyperexponential service provisioning: an economic investigation - Varshney, Shreekant; Shekhar, Chandra; Dhanunjaya Reddy, A. V.; Pritam, K. S.; Kantipudi, M. V. V. Prasad; Kotb, Hossam; AboRas, Kareem; Alqarni, Mohammed (Frontiers in Energy Research, 2023)
Authors are highly thankful to the editorial board for considering our paper for possible publication and anonymous reviewers for critical review and to give their valuable comments for updating our manuscript in present form. As per the recommendations of the Editor, the necessary changes have further been incorporated and highlighted with yellow color in the updated manuscript for a quick glance. Hopefully, the present form of the manuscript is as per the recommendation of the editorial board and can be accepted for possible publication.